Investigating a conserved role for Nanog in primordial germ cell specification - Shephard, Matthew Thomas (2010)
The specification of Primordial Germ Cells (PGCs) in early mammalian development is a fundamental process of development, critical for, maintaining the germ line. There are two methods by which PGCs are specified in the animal kingdom. Firstly, through the predetermined method involving maternally inherited germplasm, and secondly through the induction of pluripotent precursors in a process termed epigenesis. Embryoid Bodies (EBs) can be used to recapitulate early developmental processes of mammalian development, allowing the dissection and better understanding of critical processes. This project will aim to try and better understand the role of the homeobox transcription factor Nanog in specifying PGCs through the process of epigenesis. Mouse Nanog over-expression in EBs has been shown to increase PGC specification, assayed through RT-PCR analysis. The functional activity of ancestral Nanog is hypothesised to be conserved through the major trunk of evolution in organisms that specify PGCs through the induced method of epigenesis. To test this hypothesis, ancient Nanog orthologs were isolated from different positions of the Deuterostome superfamily and over-expressed in EBs. Their effects on enhancing PGC specification were then quantified through quantitative RT-PCR and western blot analysis. The results from this project show that the over-expression of ancient Nanog orthologs in mES cells can enhance the process of PGC specification, by increasing the PGC associated markers Dazl and Vasa. This suggests a possible conservation of functional Nanog activity in organisms that specify PGCs through epigenesis, and also that pluripotency is an ancient trait.